Modelling and simulation of combustion of dilute syngas fuels in a CFR engine - Padhi, Geet, author; Windom, Bret C., advisor; Olsen, Dan B., committee member; Dandy, David, committee member (Colorado State University. Libraries, 2019)
With increasing interest towards discovery of alternative fuels to act as sources of energy, many conventional internal combustion engines are being modified to operate on these new fuels. Optimization of engine specifications including compression ratio, intake/piston geometry, valve timing, and combustion phasing, can greatly improve performance when an engine is modified to operate on alternative fuels such as syngas and producer gas. However, the inability to predict the combustion characteristics of the alternative fuel, such as burn rates and auto-ignition conditions, is a significant challenge when simulation-based design of an engine is intended. The following thesis describes the development of a predictive model to simulate the combustion of a dilute syngas fuel in a Cooperative Fuel Research (CFR) spark ignited engine. The laminar flame speeds of the unique fuel mixtures calculated using CHEMKIN were coupled with the geometric features of the CFR engine to create a combustion model of the CFR engine in GT-POWER. Using two-zone modelling and detailed chemical kinetics, the model is also able to determine the performance of the engine along with any associated knocking tendency of the fuel and its corresponding operating conditions. Validation and tuning of the combustion parameters were performed through comparison to experimental pressure data taken from the CFR engine. The completed engine model can support the design and selection of operating conditions to maximize efficiency of other spark ignited internal combustion engines when powered by the dilute syngas fuel.
Keywords: engines; syngas; modelling; combustion